2022
DOI: 10.1098/rstb.2021.0222
|View full text |Cite
|
Sign up to set email alerts
|

Dosage compensation evolution in plants: theories, controversies and mechanisms

Abstract: In a minority of flowering plants, separate sexes are genetically determined by sex chromosomes. The Y chromosome has a non-recombining region that degenerates, causing a reduced expression of Y genes. In some species, the lower Y expression is accompanied by dosage compensation (DC), a mechanism that re-equalizes male and female expression and/or brings XY male expression back to its ancestral level. Here, we review work on DC in plants, which started as early as the late 1960s with cytological approaches. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 119 publications
(201 reference statements)
3
11
0
Order By: Relevance
“…In keeping with genome balance models, we observed that co-expressed WGD homeologues showed expression patterns indicative of dosage compensation 36,37 , whereas this pattern was weaker or non-existent in other duplicate classes (Fig. 3a and Extended Data Fig.…”
Section: The Effect Of Maize Wgd On Cellular Identitysupporting
confidence: 69%
“…In keeping with genome balance models, we observed that co-expressed WGD homeologues showed expression patterns indicative of dosage compensation 36,37 , whereas this pattern was weaker or non-existent in other duplicate classes (Fig. 3a and Extended Data Fig.…”
Section: The Effect Of Maize Wgd On Cellular Identitysupporting
confidence: 69%
“…A better integration of the different mechanisms of regulatory variation may also be useful, such as mechanisms based on imprinting [72] or based on reallocation of transcription factors to X-linked genes [11]. While the widespread occurrence of DC [72,73] indicates that it is needed at least for some genes, it would be interesting to introduce heterogeneity among genes in selection on dosage, and varying the genetic architecture of DC (local vs global). Several cases of interest should be investigated further, notably cases involving non-random mating [18,29,74] or UV and mating-type chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the conditions allowing the long-term maintenance of recombination suppression under the SA theory should be investigated further [following 37,38] and combined with models of regulatory evolution. Better integration of the different mechanisms of regulatory variation may also be useful, such as mechanisms based on imprinting [80] or based on the reallocation of transcription factors to X-linked genes [11]. While the widespread occurrence of DC [80,81] indicates that it is needed at least for some genes, it would be interesting to introduce heterogeneity among genes in selection on dosage, and varying the genetic architecture of DC (local vs global).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that SlWUS1 is not dosage compensated (i.e., not upregulated in males) [ 28 ] despite the location in the oldest stratum 1 [ 33 ] where we may expect dosage compensation to be prevalent, particularly given the recent models predicting that dosage compensation is responsible for evolution of X‐Y recombination repression. [ 34,35 ] This likely reflects the dosage sensitivity of SlWUS1 that should not be altered by evolving dosage compensation system. Taken together, the S. latifolia X chromosome is apparently involved in sex determination with X/Y dosage balance mechanism, that likely operates via the WUS / CLV feedback loop.…”
Section: Evolution Of Gynoecium Suppression In S Latifolia Via Two Ge...mentioning
confidence: 99%